(untitled) (Colombia Medica, 2012)
Intracystic papillary carcinoma of the breast, associated with areas of infiltration, is rare, constituting less than 1% of breast cancers. These are tumors whose initial radiological study shows lesions with low suspicion of malignancy in a high proportion of cases. We present two cases of intracystic papillary carcinoma, associated with infiltration diagnosed at the Breast Unit of Hospital Infanta Cristina In both cases, the reason for consultation was the palpation of a nodule and the initial radiographic approach showed lesions with low suspicion of malignancy